Duodenal’s perforation, a surgeon’s challenge - Ferrer, Marco Polo Tovar; Bautista, Luis Enrique Santillan; Reyes, Karina Sanchez (International Journal of Research in Medical Sciences, 2024)
Duodenal perforation (DP) represents a rare but potentially fatal condition. Delayed diagnosis and failure to provide appropriate management lead to devastating outcomes. It is known that timely treatment (<24 hours) of duodenal perforations reduces morbidity and mortality. Currently, there are multiple surgical options for managing DP, each with its respective potential complications; however, there is no consensus or national or international guidelines validating the best surgical method for treatment. This review article aims to provide the available surgical options with the lowest morbidity rates to address such a complex pathology.